A Comparative Clinical Study of Flap Thickness: Medial Sural Artery Perforator Flap Versus Anterolateral Thigh Flap - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Introduction The purpose of this study is to measure flap thicknesses of anterolateral thigh (ALT) and medial sural artery perforator (MSAP) flaps in healthy subjects by Doppler ultrasonography and compare the results in relation to sex and body mass index (BMI). Method The perforators of ALT and MSAP flaps were marked on 30 healthy subjects. The thickness of skin and subcutaneous tissue was measured in millimeters at the site of the perforator using Doppler ultrasonography. Results The mean SD age of the participants was 36.4 +/- 10.5, the mean +/- SD BMI was 25.2 +/- 3.9 (19.4-32.5). The mean +/- SD flap thickness was 11.55 +/- 4.38 mm for ALT and 8.31 +/- 3.6 mm mm for MSAP (P < 0.01). Anterolateral thigh flap was significantly thicker than MSAP in both males (9.02 vs 6.11 mm) and females (14.07 vs 10.52 mm) (P < 0.05). The thickness of both MSAP and ALT flap had a positive correlation with BMI. The relationship was stronger for ALT in males (r = 0.66 for ALT, r = 0.59 for MSAP) and for MSAP in females (r = 0.70 for ALT, r = 0.83 for MSAP). Discussion This study confirms that MSAP flap is thinner than ALT and the results correlate with BMI. Therefore, MSAP flap can be considered a good alternative to ALT, to avoid bulk, in reconstruction of shallower soft tissue defects.
Keywords: anterolateral thigh flap; medial sural artery flap; flap thickness; RADIAL FOREARM FLAP; DONOR-SITE; NECK DEFECTS; ANATOMIC BASIS; RECONSTRUCTION; HEAD; VERSATILITY; EXPERIENCE; MORBIDITY; CANCER